A novel mechanism of functional cooperativity regulation by thiol redox status in a dimeric inorganic pyrophosphatase - Costa, E.P.; Façanha, A.R.; Cruz, C.S.; Silva, J.N.; Machado, J.A.; Carvalho, G.M.; Fernandes, M.R.; Martins, R.; Campos, E.; Romeiro, N.C.; Githaka, Naftaly W.; Konnai, S.; et al. (Elsevier, 2017)
Inorganic PPases are essential metal-dependent enzymes that convert pyrophosphate into orthophosphate. This reaction is quite exergonic and provides a thermodynamic advantage for many ATP-driven biosynthetic reactions. We have previously demonstrated that cytosolic PPase from R. microplus embryos is an atypical Family I PPase. Here, we explored the functional role of the cysteine residues located at the homodimer interface, its redox sensitivity, as well as structural and kinetic parameters related to thiol redox status. Methods In this work, we used prokaryotic expression system for recombinant protein overexpression, biochemical approaches to assess kinetic parameters, ticks embryos and computational approaches to analyze and predict critical amino acids as well as physicochemical properties at the homodimer interface. Results Cysteine 339, located at the homodimer interface, was found to play an important role in stabilizing a functional cooperativity between the two catalytic sites, as indicated by kinetics and Hill coefficient analyses of the WT-rBmPPase. WT-rBmPPase activity was up-regulated by physiological antioxidant molecules such as reduced glutathione and ascorbic acid. On the other hand, hydrogen peroxide at physiological concentrations decreased the affinity of WT-rBmPPase for its substrate (PPi), probably by inducing disulfide bridge formation. Conclusions Our results provide a new angle in understanding redox control by disulfide bonds formation in enzymes from hematophagous arthropods. The reversibility of the down-regulation is dependent on hydrophobic interactions at the dimer interface. General significance This study is the first report on a soluble PPase where dimeric cooperativity is regulated by a redox mechanism, according to cysteine redox status.